Síntesis, caracterización y propiedades ópticas no lineales de Nanopartículas de Titanato de Bario obtenidas mediante el método del Peróxido - Sernaqué Torres, Cristhian Joel (2021)
In the present research work, barium titanate nanoparticles were synthesized by the_x000D_ peroxide method in order to evaluate the influence of the annealing temperature of 700,_x000D_ 800 and 900 degrees Celsius on their crystalline structure and intensity of non-linear_x000D_ optical response. As precursor materials, titanium trichloride-15.5 percent and dihydrated_x000D_ barium chloride were used. Ultrapure water and hydrogen peroxide-30 percent were used_x000D_ as solvents. The pH was modified to 9.98 by adding aliquots of ammonium hydroxide_x000D_ solution. The X-ray diffraction patterns of the powder sample annealed at 900 degrees_x000D_ Celsius, revealed characteristic diffraction peaks of the ferroelectric tetragonal phase of_x000D_ barium titanate, without the presence of other impurities and with an average crystallite_x000D_ size of 34.2 nm; while the samples of annealed powder at 700 and 800 degrees Celsius,_x000D_ also showed other peaks corresponding to the cubic phase and impurities, possibly from_x000D_ barium polythitanates. SEM images and EDS spectra revealed that barium titanate_x000D_ nanoparticles, with an average diameter of 50 nm, are in the form of agglomerates. The_x000D_ non-linear optical response intensity spectra, obtained with a pulsed laser of 1064 nm_x000D_ wavelength and pulse energy of 2.78 mJ, showed that Barium Titanate nanoparticles_x000D_ annealed at 900 degrees Celsius had a non-linear optical response in the wavelength of_x000D_ 532.4 nm, with an intensity approximately 3 times greater than nanoparticles annealed at_x000D_ 800 degrees Celsius. Barium Titanate nanoparticles, annealed at 700 degrees Celsius,_x000D_ did not show significant non-linear optical response, due to a low presence of the_x000D_ tetragonal phase.